STUDY OF CHEMICAL PROPERTIES AND PEAT SOIL FERTILITY STATUS IN SOME TYPES OF LAND USE IN SUB-DISTRICT RASAU JAYA KUBU RAYA DISTRICT - Sardika Fahmi; Asrifin Aspan; Urai Edi Suryadi (Jurnal Sains Pertanian Equator, 2019)
Based on West Kalimantan BPS data for 2017, West Kalimantan has 1,543,752 ha of peatlands spread across several districts. One district that has peatlands is Kubu Raya Regency where the peatlands in this region are 130,248 ha. the purpose of this study was to determine the chemical nature of the soil and the fertility status of peat soils in several types of land use for oil palm, rubber, and horticulture.The location of this research is in Rasau Jaya III Village, Rasau Jaya Sub-District, Kubu Raya District. This research was conducted from May to July from the start of preparation, field sampling, soil analysis in the laboratory to the presentation of results. The parameters in this study are, ground water table, pyrite, N-total, P-total, K-total, C-organic, soil pH, C/N ratio, cation exchange capacity, base saturation and bulk density.The results of the analysis showed that the ground water table in the upper layer in each study area included shallow criteria while for the lower layer had rather deep criteria. Pyrite at the study site was no sulfidic. N-total between 0.21-0.45% with very low criteria. P-total between 0.93-3.94 mg / 100g with very low to low criteria. K-total between 0.98-3.98 mg / 100g with very low to low criteria. C-Organic between 4.94-12.96 mg / 100g with very high criteria. Soil pH between 2.65-3.01 with very acid criteria. C/N Ratio between 1.03-5.70% with very low criteria. Cation exchange capacity between 60.74-103.82 cmol (+) kg-1 with very high criteria. Base saturation between 9.41-16.58% with very low criteria. Bulk density from 0.15-0.34 gram / cm3. From the results of this analysis obtained criteria of soil fertility which are classified as low criteria.       Keywords: Chemical properties, fertility status  peat soils